STRATEGI PENGEMBANGAN MUARA SUNGAI YEH MATAN SEBAGAI OBJEK WISATA AIR DI DESA TEGAL MENGKEB KECAMATAN SELEMADEG TIMUR KABUPATEN TABANAN - Agung, Anak Agung Putu (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract One of the development in tourism industry can be done by develop the tourist destination as a tourist attraction. Development of tourist attraction is certainly planned and implemented in accordance with the potential and capabilities of the region. One of alternative to develop the tourist attraction and able to be selected as the tourist destination especially in Tegal Mengkeb village is water attraction at estuary of Yeh Matan river which related to nature tourism. The used method in this study is a combination between qualitative and quantitative research method, data collection techniques by questionnaires, interviews, literature study and documentation. Data analysis techniques using SWOT analysis to determine the internal and external factors position in development of yeh matan estuary as water attraction. The results of research according to SWOT analysis obtained the average value for internal factor is 3,057 and external factor is 3,024. It means that the estuary of Yeh Matan river are in a favorable position, maintain and control, maintain the condition of internal factor that have existed without make changes as water attraction. Require the cooperation and integrated partnership among community, village officials, Government of Tabanan Regency and related stakeholders to promote the estuary of Yeh Matan river as water attraction at Tegal Mengkeb village, East Selemadeg Sub District, Tabanan Regency.
Keywords: Key words : nature tourism, water attraction, development strategy, estuary.